Avascular necrosis in systemic lupus erythematosus: total hip replacement in a patient with mutation in clotting factor V (Leiden) gene, clinical observation - F. A. Cheldieva; I. G. Kushnareva; V. V. Babak; A. E. Khramov; T. M. Reshetnyak (Современная ревматология, 2021)
The article provides a description of the systemic lupus erythematosus patient with multiple avascular bone necrosis (ABN), homozygous mutation in clotting factor V (Leiden) gene, who successfully underwent the total hip replacement. The role of high doses of glucocorticoids and coagulation disorders, in particular the homozygous mutation in factor V (Leiden) gene, in the development of ABN is discussed.